Analisis Kreativitas Guru Pada Mata Pelajaran IPS SD Negeri 1 Passo: Indonesia - Samla Dokolamo; Ode Abdurrachman; Elsinora Mahananingtyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyse teacher creativity in social studies subjects at SD Negeri 1 Passo. the type of research used is descriptive qualitative research. The data sources used are primary data sources and secondary data. The data collection techniques used were observation, interview and documentation. While data analysis techniques using data reduction, presentation and verification techniques. The results showed that the form of teacher creativity in improving the learning outcomes of SD Negeri 1 Passo students in social studies subjects is in accordance with the applicable curriculum, while the form of teacher creativity on learning outcomes has been running well. To get learning outcomes using teaching modules, learning methods. there are some shortcomings in terms of learning such as the use of learning approaches but this can be overcome by the school, so that learning can be run according to applicable regulations.